Records managers – obligation to pass the professional exam - Todorović Bilić, Marijana (Moderna arhivistika, 2024)
Records managers at the creators of archives are defined by the archival legislation of the Republic of Srpska, The Law on Archives and the Regulations on record management for administrative bodies. Records managers are officials of different degrees and fields of education. Given that there are no high schools in Bosnia and Herzegovina that deal with the training of archival technicians, the education of officials is carried out through the preparation for passing professional exams in the Archives of the Republic of Srpska according to the planned program, and constant professional development through seminars/trainings provided for records managers. It is very important to employ an expert person, qualified to manage records and monitor information and technological development. Professional training and improvement are of the greatest importance for the protection of public records, especially at a time when it is necessary to follow technological and informational development. Since 2002, the Archives of the Republic of Srpska and the Association of Archivists of the Republic of Srpska have launched a program of taking professional exams for records managers. In the period from March 2002 to January 2024, a total of 300 candidates passed the professional exam for working on the protection of public records and archival materials. The plan and program of taking professional exams for records managers is regulated by the "Regulations on conditions, deadlines and methods of taking professional archival exams, recognition of professional archival titles and conditions for acquiring professional archival titles".
Keywords: archival legislation; arhivska zakonodaja; professional exam; professional training; records; records manager; strokovni izpit; strokovno usposabljanje; upravljavci dokumentov z zapisi